Estudio de factibilidad para la creación de un hotel en la parroquia el Ingenio del cantón Espíndola, provincia de Loja. - Belduma Calva, Juan Diego (2024)
The main objective of the Curricular Integration project is to evaluate the feasibility of establishing a hotel in the parish of El Ingenio, with the intention of offering a new and innovative tourist service for tourists. The procedure used for fulfillment of the study of the market was carried out through the application of surveys, interviews and observations, enabling the determination of viability in the market, the study of the offer related to the hotel service was also established. Subsequently, the technical study was carried out, in which an analysis was made of macro and micro location factors, so it was established that the micro location was in the parish El Ingenio, as well as the installed capacity of the project will be 80%, an average of 8,736 people a year. The economic-financial study determines for fixed assets a total of $68,980.00, deferred assets of $4,207.50 and working capital of $3,002.07 giving a total investment of $76,189.57, which will be financed in its entirety by the investor, a discount rate of 16.00%, considering a fixed-term benchmark passive rate of 7.74% and an investment risk of 8.26%, during this evaluation it was applied various indicators, determining its feasibility from the Net Present Value (NPV) with a total of $35,149.84, an Internal Rate of Return (IRR) of 28.05%, the Cost Benefit Ratio (RBC) of 0.62 cents, a Cost of Opportunity (WACC) of 16.00% and the Capital Recovery Period (PRC) of three years, seven months and twenty-eight days, therefore, according to the indicators it is determined that the project is viable from the economic side.